Study on Point Spread Function of Perovskite Fast Neutron Scintillation Imaging Screen - FENG Zhelin1, LIU Linyue2, SONG Yan2, DUAN Baojun2, BAO Zizhen3, OUYANG Xiaoping2 (Yuanzineng kexue jishu, 2025)
Perovskite scintillator materials exhibit high hydrogen content, photo yield and linear energy response, rendering them ideal materials for the fabrication of fast neutron radiation imaging screens. However, efficient screening of new scintillator imaging screen materials presents challenges due to the high cost of material preparation and performance testing, long cycle time, and large workload. Additionally, the limited availability of experimental machines for fast neutron imaging and the high cost of imaging systems hinders the efficient detection of large number of materials by using common fast neutron sources. The point spread function, which serves as a critical parameter for evaluating the imaging capability of scintillators, can be defined as the projected distribution of the energy deposited by a single vertical incident radiation on the exit plane of a thin scintillator. The point spread function can be used for theoretical simulation of the scintillator imaging capability. The design and screening of perovskite scintillator imaging screening materials and the estimation of fast neutron imaging performance through theoretical simulations are important for the development of perovskite scintillator-based fast neutron imaging technologies. At present, there is little research on the point spread function of perovskite scintillators. Therefore, with the help of their fast neutron imaging properties, it is necessary to simulate new materials, establish and develop the point spread function research methods, and promote the fast neutron imaging technology of perovskite scintillator materials. In this study, Geant4 and Matlab were used to build a physics model of fast neutron imaging, Monte Carlo methods were used to simulate the energy deposition distribution of fast neutrons in the scintillator, and the point spread function simulation results of various perovskite scintillators were carried out. The point spread functions of Pb and Cu based perovskite scintillators were simulated and calculated under various neutron and X-ray irradiation conditions. By comparing the trends of point spread function at different conditions, it is found that the half-width of the point spread function of perovskite scintillator material decreases with the increase of neutron energy. In addition, the simulation transformation results of C5H7Cu2I2N4’s experimental imaging photo are obtained by using this model, showing a consistent trend on the luminescence characteristics with the experimental results. The computational approach to the point spread function can theoretically assess the neutron imaging capability of the new perovskite fast neutron scintillator screens, providing valuable guidance for the study of novel neutron imaging screen materials and fast neutron imaging experiments.